Influence of interaction on accuracy of quantification of mixed microplastics using Py-GC/MS. Issue 3 (June 2022) - Lou, Fangfang; Wang, Jun; Sun, Chen; Song, Jiaxing; Wang, Wanli; Pan, Yuhan; Huang, Qunxing; Yan, Jianhua
Abstract: Accurate identification and quantification are very challenging and extremely important in evaluating microplastic (MP) pollution. Although pyrolysis-based MP measurement methods have attracted intensive interest due to their great potential for rapid qualitative and quantitative analysis, the influence of thermochemical interactions during co-pyrolysis of different plastics has not been addressed. In the present study, five common MP materials, polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), and polymethyl methacrylate (PMMA), were detected using pyrolysis gas chromatography mass spectrometry (Py-GC/MS). The existence of interactions was confirmed by comparing the experimental results of individual and mixed pyrolysis. Upon the specific analysis of the impact on the quantitative calculation, we found that some indicators selected in previous studies may lead to high uncertainty, exceeding 100%. On this basis, new indicators with better reliability were proposed for the quantitative analysis of mixed MP samples, including 1- octadecene, pentane, and bibenzyl. Finally, the maximum quantification uncertainties of PE, PP, and PS were reduced from 91–25%, 130–32%, and 93–24%, respectively. The present study can provide a reference for improving the accuracy of quantitative analysis of mixed MPs. Graphical Abstract: ga1 Highlights: For 5 common microplastics components, co-pyrolysis interactions are widespread. PP and PS have strong interaction when co-pyrolyzed with other plastics. Original quantitation indicators may lead to more than 100% uncertainties. New quantitation indicators were selected for PE, PP and PS. Maximum quantitation uncertainties of PS were reduced from 93–24%.